New insights into the role of spermine in Arabidopsis thaliana under long-term salt stress - Alet, Analía Inés (2012)
Polyamines (putrescine, spermidine and spermine) are traditionally implicated in the response of plants to environmental cues. Free spermine accumulation has been suggested as a particular feature of long-term salt stress, and in the model plant Arabidopsis thaliana the spermine synthase gene (AtSPMS) has been reported as inducible by abscisic acid (ABA) and acute salt stress treatments. With the aim to unravel the physiological role of free spermine during salinity, we analyzed polyamine metabolism in A. thaliana salt-hypersensitive sos mutants (salt overlay sensitive; sos1-1, sos2-1 and sos3-1), and studied the salt stress tolerance of the mutants in spermine and thermospermine synthesis (acl5-1, spms-1 and acl5-1/spms-1). Results presented here indicate that induction in polyamine metabolism is a SOS-independent response to salinity and is globally over-induced in a sensitive background. In addition, under long-term salinity, the mutants in the synthesis of spermine and thermospermine (acl5-1, spms-1 and double acl5-1/spms-1) accumulated more Na+ and performed worst than WT in survival experiments. Therefore, support is given to a role for these higher polyamines in salt tolerance mechanisms.